2014
DOI: 10.1111/1756-185x.12535
|View full text |Cite
|
Sign up to set email alerts
|

Trikatu, a herbal compound mitigates the biochemical and immunological complications in adjuvant-induced arthritic rats

Abstract: These results suggest that trikatu could be a promising alternative drug for the control and management of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The observed lipid profile is in accordance with previous studies on AIA rats, as well as in RA patients (Hendawy et al 2015 ; Murunikkara and Rasool 2017 ; Curtis et al 2012 ). Although conflicting results were reported for TC and LDL-C levels across the time course of the RA disease, cardioprotective HDL-C is of particular interest in the context of active inflammation, as its levels dramatically fall and are persistently low, to a far greater extent than the changes seen in other lipid components.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed lipid profile is in accordance with previous studies on AIA rats, as well as in RA patients (Hendawy et al 2015 ; Murunikkara and Rasool 2017 ; Curtis et al 2012 ). Although conflicting results were reported for TC and LDL-C levels across the time course of the RA disease, cardioprotective HDL-C is of particular interest in the context of active inflammation, as its levels dramatically fall and are persistently low, to a far greater extent than the changes seen in other lipid components.…”
Section: Discussionsupporting
confidence: 92%
“…Although conflicting results were reported for TC and LDL-C levels across the time course of the RA disease, cardioprotective HDL-C is of particular interest in the context of active inflammation, as its levels dramatically fall and are persistently low, to a far greater extent than the changes seen in other lipid components. Several studies have confirmed an inverse correlation between inflammatory markers, such as CRP and HDL-C (Murunikkara and Rasool 2017). Others reported that RA leads to a more atherogenic lipid profile in the form of increased atherogenic index 'TC/HDL and LDL/ HDL ratios' that constitutes an important CVD prognostic marker (Parveen et al 2016;Popa et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Various details manifest the capability of Trikatu in managing inflammatory disorders such as RA. It slows down the making of inflammatory cytokines, pain mediators, osteoclastogenic factors in adjuvant-induced arthritis [88].…”
Section: Trikatumentioning
confidence: 99%
“…Consequently, it has become an inevitable trend to identify an effective anti-RA drug with high therapeutic effects and fewer side effects. The search for traditional herbal drugs that are more effective, safer, and economical has attracted a great attention, since 80% of the world population mainly rely on herbal drugs [ 13 ]. With the long history of traditional Chinese medicine (TCM) in the treatment of RA, RA is included in the theory of TCM “arthralgia” category.…”
Section: Introductionmentioning
confidence: 99%